Decentralised strategy for energy management of collaborative microgrids using multi‐agent system. Issue 6 (5th July 2022) - El Zerk, Abdallah; Ouassaid, Mohammed; Zidani, Youssef
Abstract: In this study, the concept of collaborative microgrids (MGs) with shareable resources is introduced. The developed concept enables the householders of an isolated district or neighbourhood to cooperate and communicate intelligently in order to establish a reliable and proprietary MG. Therefore, a multi‐agent system solution for a distributed energy management system is designed. The proposed approach should first supply households while maintaining MG stability. Second, it offers designers decent programing flexibility and ensures system adaptability when households are added or removed. Three agents are developed, the nanogrid (NG) agent which handles the centralised energy management of the NG and messages the Master agent with the necessary information. The Master agent is responsible for the decentralised management of energy over the microgrid and controls the switches. The management strategy using multi‐agent systems aims to encourage customers considered as NG to contribute energy to the MG. The strategy relies on the implementation of a point‐based remuneration model in which the collected points depend on the contribution. The results highlight the importance of the proposed approach, which can be exploited to connect and supply isolated facilities intelligently.